A guide to modern inorganic chemistry - Steven M Owen (Longman, 1991)
This book emphasizes the principles and trends in the chemistry of the elements. It comprises the essentials of structure, bonding and reactivity; a unifield descriptive account of main group and transition metal chemistry; and a selection of special topics, including spectroscopy in inorganic chemistry. Worked examples are fully integrated into the book, and there are model answers to typical examination problems